The effects of tourist’s perceived experience risk, satisfaction, and intention to revisit the heritage destination in Pulau Pinang - Bilal, Muhammad; Ahmad, Khairun Najiah; Abas, Siti Aisah; Ahmad , Nurul Aziah; Ngelambong, Anderson Anak (International Journal of Psychosocial Rehabilitation, 2020)
The issue of risks is a major dilemma in tourism studies. Abundance preceding studies in tourism focused on the issue of risk in the tourism industry such as safety and security, financial, health, environmental, and economic. However, there are relatively limited studies on the issue of experience risk in tourism, particularly in a heritage tourism context. As a segment in the tourism industry, which is synonymous with fragility and intangibility, heritage tourism primarily involves with consumption of experience. The issue of experience is a significant concern in heritage tourism, due to it dealing with complicated tourist that solely seeks for novelty experience in when travelling to a heritage destination. Risk frequently occurs, no matter how much the knowledge and information towards the destination that the tourist has, yet there is still a room for risk to turn out. In the milieu of the present study, the risk for experience might occur even though the tourist has prepared with a lot of information and knowledge if the managerial level is ignoring the need to preserve and maintain the quality of the heritage products. Personally-administered questionnaires were distributed to tourists who travelled to heritage destinations in Pulau Pinang. Results showed perceived experience risk has a significant negative relationship on tourists’ revisit intention while satisfaction did not mediate the relationship between perceived experience risk and revisit intention. The implications of these results for understanding the effects of perceived experience risk and intention to revisit heritage destinations in Pulau Pinang are discussed.